2002
DOI: 10.1021/jp020740p
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Field Shift Effect in the Isotope Exchange Reaction of Chromium(III) Using a Crown Ether

Abstract: Chromium isotopes were fractionated by the liquid-liquid extraction system using dicyclohexano-18-crown-6. We found a mass-independent isotope effect that the intermediate isotope of 52 Cr was enriched in the organic phase. Because of its magic number neutrons N ) 28, 52 Cr has the smallest nuclear charge distribution in naturally occurring chromium isotopes. The enrichment property gives the confident experimental fact of the nuclear field shift effect in the new Bigeleisen theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For many elements (Ti, Cr, Zn, Ba, Sm, Nd, Gd, Mo, Te, Sn, and Ru), the existence of mass-independent isotope effects is consistent with this theory. These have been confirmed experimentally by chemical exchange methods (solvent extraction or liquid chromatography) with macrocyclic compounds (Fujii et al 1998a(Fujii et al , 1998b(Fujii et al , 1999(Fujii et al , 2001(Fujii et al , 2002a(Fujii et al , 2002b(Fujii et al , 2006bMoynier et al 2008Moynier et al , 2009.…”
Section: Theoretical Background On the Nuclear Field Shift Effectmentioning
confidence: 72%
“…For many elements (Ti, Cr, Zn, Ba, Sm, Nd, Gd, Mo, Te, Sn, and Ru), the existence of mass-independent isotope effects is consistent with this theory. These have been confirmed experimentally by chemical exchange methods (solvent extraction or liquid chromatography) with macrocyclic compounds (Fujii et al 1998a(Fujii et al , 1998b(Fujii et al , 1999(Fujii et al , 2001(Fujii et al , 2002a(Fujii et al , 2002b(Fujii et al , 2006bMoynier et al 2008Moynier et al , 2009.…”
Section: Theoretical Background On the Nuclear Field Shift Effectmentioning
confidence: 72%
“…These effects may be restricted to very heavy elements (i.e., uranium). Claims of non-vibrational fractionations (Fujii et al 2002) in lighter elements have not been substantiated using modern analytical techniques, to my knowledge, and it is not yet clear how important these unconventional mechanisms are in natural systems. For this reason, the present review focuses on the well established vibrational model (Bigeleisen and Mayer 1947;Urey 1947).…”
Section: Other Causes Of Equilibrium Isotopic Fractionationmentioning
confidence: 96%
“…The elements studied include lithium, 1) magnesium, 2) zinc, 3) nickel, 4) samarium, 5) neodymium, 6) gadolinium, 7) strontium, 8) barium, 9,10) chromium, 11) iron, 12) molybdenum, 13) and hafnium. 14) These studies revealed that crown ethers often show large isotope effects, indicating that they could provide isotope separation systems with high performance.…”
Section: Introductionmentioning
confidence: 99%